2021
DOI: 10.1038/s41393-020-00576-3
|View full text |Cite
|
Sign up to set email alerts
|

Detecting subgroups in social participation among individuals living with spinal cord injury: a longitudinal analysis of community survey data

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(58 reference statements)
2
3
0
Order By: Relevance
“…Also, female patients have cultural issues in the Chinese society, which leads to poor quality of life (6). The findings of the current study agree with those of cross-sectional studies on the Jordan population (1), Iranian population (22), and Chinese population (6) with traumatic spinal cord injuries and with those of longitudinal multicenter studies on the European population (15,23). The strengths and weaknesses of patients after spinal cord injuries must be taken into account to improve the quality of life of patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, female patients have cultural issues in the Chinese society, which leads to poor quality of life (6). The findings of the current study agree with those of cross-sectional studies on the Jordan population (1), Iranian population (22), and Chinese population (6) with traumatic spinal cord injuries and with those of longitudinal multicenter studies on the European population (15,23). The strengths and weaknesses of patients after spinal cord injuries must be taken into account to improve the quality of life of patients.…”
Section: Discussionsupporting
confidence: 87%
“…Rehabilitation can decrease dependency even in the highest level of injury. Better health-related conditions and financial aspects improve the quality of life of patients with spinal cord injuries (15).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other studies, SCI was common in the early middle-aged population (Brinkhof et al 2016 ; Madasa et al 2020 ; Pefile, Mothabeng & Naidoo 2018 ). The average age of people living with SCI is like local findings (Joseph & Nilsson Wikmar 2016 ) and is much younger compared to international findings (Gross-Hemmi et al 2021 ). We must note that we did not find a significant association between age and the presence of pain, like findings by Hassanijirdehi et al ( 2015 ).…”
Section: Discussionsupporting
confidence: 49%
“…Nevertheless, many of the mentioned aspects-for example, the presence of muscle spasms in participants with SCI/D, pain, and bowel and bladder management issueswere already part of the most important research topics and research plans for adults and could be specifically addressed in younger people [1]. Recent research concerning access to health services has been conducted utilizing new methodological concepts and health system interventions that can be used to optimize the satisfaction of young people and families living with SCI/D or SB [19,40]. The results obtained for mobility and accessibility showed that these domains play an important role in the young people's and parents' everyday lives.…”
Section: Importance Satisfaction and Research Prioritiesmentioning
confidence: 99%